SURFACE MODIFICATION OF INORGANIC MEMBRANE BY GRAFTING - Velianti
Ceramic membranes are famous for their high thermal and mechanical stabilities. Many applications such as waste water removal and membrane reactors can rely only on hydrophilic nature of ceramic membranes. But for nonpolar gases mixture separation, the hydrophilic nature will become limitation of ceramic membranes applications To increase the solubility-based gas separation of the light organic gases, hydrophobic groups were grafted onto alumina membranes surface. Trichloromethylsilane (TCMS) was used as a precursor for grafting reaction. As a result of grafting reaction the hydrophilic nature of the surface will change into hydrophobic. Polymerization of TCMS is occurred in presence of the excess water. Therefore, as a side effect, the alumina membrane pore diameter will be decreased by partially blocking. In this experiment the effect of the TCMS (trichloromethylsilane) concentration, reaction temperature and reaction time was studied to control the pore blocking obtained from silanization reaction by using both solution phase method and vapor phase method. We demonstrated the important parameters effecting process. It is shown that many parameters were affected the grafting reaction. Contact angle, X-ray Photoelectron Spectroscopy, Scanning Electron Microscopy were used to characterize the membrane. Overall, the vapor phase method was resulted in thinner silane layer on top of the membrane surface compared to the solution phase method and also controlled reduced pore blocking on ?-Al2O3 powder. Silanization on the oxide surface of Si wafer also performed to simplify the study about TCMS grafting. The vapor phase method gave smoother silane layer while the solution phase method gave more silane roughness.